Search for New Resonances Decaying to Pairs of Merged Diphotons in Proton-Proton Collisions at sqrt[s]=13 TeV - Hayrapetyan, A; Tumasyan, A; Adam, W; Andrejkovic, J W; Bergauer, T; Chatterjee, S; Damanakis, K; Dragicevic, M; Hussain, P S; Jeitler, M; Krammer, N; Li, A; et al. (Physical review letters, 2025)
A search is presented for an extended Higgs sector with two new particles, X and ϕ, in the process X→ϕϕ→(γγ)(γγ). Novel neural networks classify events with diphotons that are merged and determine the diphoton masses. The search uses LHC proton-proton collision data at sqrt[s]=13 TeV collected with the CMS detector, corresponding to an integrated luminosity of 138 fb^{-1}. No evidence of such resonances is seen. Upper limits are set on the production cross section for m_{X} between 300 and 3000 GeV and m_{ϕ}/m_{X} between 0.5% and 2.5%, representing the most sensitive search in this channel.